Tinjauan Pustaka Sistematis Penerapan Quality Function Deployment di Industri Manufaktur - Ing Brian Rapelo; Krisna Ananda Priyatama; M. Bari Baihaqi; M. Rizki Darmawan; Rohmat Setiawan; Indra Setiawan (Jurnal Optimalisasi, 2023)
Quality Function Deployment (QFD) is a tool or planning instrument that is used to provide an overview of customer desires which are then translated into strategic stages to produce products or services whose characteristics are in accordance with customer wishes. The advantage of this method approach is that the level of customer satisfaction can be explained through data, so that improving the quality of services or products and periodic evaluations to correct deficiencies can be carried out in accordance with the customer's assessment. Many studies using the QFD method are carried out by the industry. This literature review aims to analyze the advantages of the QFD method for increasing customer satisfaction in the manufacturing industry. The method used is the Systematic Literature Review. This article involves a study review of 24 articles related to the application of QFD in the manufacturing industry. The study was conducted using the Google Schoolar database. The articles obtained were then summarized, classified, and comprehensively reviewed. This article expands the knowledge and study of the application of QFD in the manufacturing industry. The development of QFD in future research can be carried out in cross-fields that still have links. QFD results can be a tool for making improvements based on the needs or voice of the customer. Improvements made using the QFD method can increase customer satisfaction, increase profits and marketing, improve service quality, and improve product quality.